Tissue engineering perspectives in dentistry: review of the literature - Juliana da Silva MORO; Raquel Cristine Silva BARCELOS; Thiago Gomes TERRA; Cristiane Cademartori DANESI (Faculdade São Leopoldo Mandic, 2018)
Tooth losses due to pathological processes continue to be a reality in daily clinical dentistry, inducing functional and psychological complications in patients. In view of this, a new option for the management of this problem - tissue engineering - has been studied in Dentistry. This field, considered multidisciplinary, uses three key elements for tissue regeneration: scaffolds (extracellular matrices) - natural or synthetic; cells, and growth factors. In this sense, combination of these three elements may induce regeneration of the dental pulp, bone and periodontal tissue, among others. Therefore, the aim of this study was to conduct a literature review, describing the main elements of tissue engineering and their applicability in Dentistry, as a means of updating dental surgeons about this subject.